2005
DOI: 10.1142/s0218001405003971
|View full text |Cite
|
Sign up to set email alerts
|

Transductive Learning for Short-Text Classification Problems Using Latent Semantic Indexing

Abstract: This paper presents work that uses Transductive Latent Semantic Indexing (LSI) for text classification. In addition to relying on labeled training data, we improve classification accuracy by incorporating the set of test examples in the classification process. Rather than performing LSI's singular value decomposition (SVD) process solely on the training data, we instead use an expanded term-by-document matrix that includes both the labeled data as well as any available test examples. We report the performance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…However, it is unrealistic to query the search engine for each document for the great amount of documents, which is expensive. Another way is to utilize online data repositories, such as Wikipedia [16] and ODP [17], as external knowledge sources [10,11]. This method is more useful and practical.…”
Section: Introductionmentioning
confidence: 99%
“…However, it is unrealistic to query the search engine for each document for the great amount of documents, which is expensive. Another way is to utilize online data repositories, such as Wikipedia [16] and ODP [17], as external knowledge sources [10,11]. This method is more useful and practical.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, traditional text classification methods cannot be applied to short-text classification better. An effective way of short-text classification is to use some extra information to assist classification [1][2]. Some methods has already achieved certain effect, one of which is based on hyponymy relation and is proposed by Sheng Wang [3] and another one is Agent and Patient Relation Acquisition for Short-text Classification which is proposed by Dingbang Wei [4].…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the particular case of short text classification has been investigated in the past in various research projects from both, a categorization and a clustering perspective. In [153], for instance, it is described a method for improving the classification of short text strings by using a combination of labeled training data, plus a secondary corpus of unlabeled but related longer documents. It is shown that such unlabeled background problems [154].…”
Section: Related Workmentioning
confidence: 99%
“…In [153], for instance, it is described a method for improving the classification of short text strings by using a combination of labeled training data, plus a secondary corpus of unlabeled but related longer documents. It is shown that such unlabeled background problems [154]. LSI is a technique that allows to find a low-rank approximation to a original term-document matrix (describing the occurrences of terms in documents).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation